STUDY OF THE MAIN CAUSES OF ANXIETY AND STRESS AMONG TEACHERS AND POSSIBLE SOLUTIONS - Singh, Dharmendra; Jain, Vinod Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
The aim of this research paper is to identify and analyse the main causes of anxiety and stress among teachers. Anxiety and stress among school teachers is a serious issue. The work area of ​​teachers is challenging and they have to face various types of stress. Teachers not only have to fulfil academic responsibilities, but also have to deal with administrative work, expectations of students and parents and challenges of personal life. This has a direct impact on their teaching and learning process. To remove anxiety and stress among teachers, governments and educational organisations need to take steps to encourage their energy, support training and strengthen the support system. This will not only improve the anxiety and stress of teachers but will also pave the way for advancement in the education sector and better education for students. This research presents an overview of the impact of these factors on the mental health of teachers. As a possible solution to this problem, maintaining work-life balance, time management, administrative support, counselling services, mental health measures like yoga and meditation and regular training programs for teachers are important. A positive atmosphere and supportive culture in schools can also help in reducing anxiety and stress. Empowerment of teachers and a respectful environment lay the foundation for an anxiety and stress-free educational system.